Assembleias fitoplanctônicas no gradiente longitudinal barragem-jusante do reservatório de Itaipu, rio Paraná (Brasil/Paraguai) - Matsuura, Patricia [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The freshwater phytoplankton, responsible for a significant part of primary production in rivers and lakes, is of great importance for matter and energy available to other trophic levels of structuring aquatic food chains. In recent decades, the construction of dams, especially for the generation of electricity, produced changes not only in physical and chemical characteristics of rivers, but also in biocoenosis of these ecosystems. Thus, research is needed to expand the basic knowledge about these environments and subsidize actions appropriate conservation and management. Considering that lotic environments are relatively little studied, and the river-reservoir interaction, the work aims to analyze the limnological conditions and assemblies phytoplankton along the gradient established by the Itaipu reservoir and downstream stretch of the Paraná River. During two periods of the year, winter and summer, we analyzed nine sampling stations: one in lentic environment (the dam), six on the Parana River (each 5 km), at the mouth of a river Monday and another at the mouth of the Iguazu river. The phytoplankton community was composed of 315 taxa, with the class Bacillariophyceae most specious. At every point the richness was higher in summer and with a longitudinal trend in the increasing points after falling after the dam and the contribution of the tributaries. The number of taxa common to the three rivers was low in both study periods. The higher taxa can be explained by the variety of environments sampled, different residence times of water and nutrient concentrations, whereas the rivers Iguazu and Monday suffer high human influence. The greater abundance of organisms in the dam, in both periods, it should be the class Cryptophyceae contributing over 75% of total phytoplankton in point. In cluster analysis (composition and abundance)...(Complete abstract click electronic access below)

O fitoplâncton de água doce, responsável por parte significativa da produção primária de rios e lagos, é de grande importância por disponibilizar matéria e energia aos demais níveis tróficos estruturadores das cadeias alimentares aquáticas. Nas últimas décadas, a construção de represas, principalmente para a geração de energia elétrica, promoveu modificações não somente nas características físicas e químicas dos rios, como também nas biocenoses destes ecossistemas. Assim, são necessárias pesquisas que ampliem o conhecimento básico sobre esses ambientes e subsidiem ações adequadas de conservação e manejo. Considerando que ambientes lóticos são relativamente pouco estudados, bem como a interação rio-reservatório, o trabalho visou analisar as condições limnológicas e assembleias fitoplânctônicas ao longo do gradiente estabelecido pelo reservatório de Itaipu e trecho de jusante no rio Paraná. Durante dois períodos do ano, inverno e verão, foram analisadas 9 estações de amostragem: uma em ambiente lêntico (montante da barragem), seis no rio Paraná (a cada 5km), uma na foz do rio Monday e outra na foz do rio Iguaçu. A comunidade fitoplanctônica foi composta por 315 táxons, sendo Bacillariophyceae a classe mais especiosa. Em todos os pontos a riqueza foi maior no verão e com uma tendência longitudinal crescente nos pontos após a barragem e decrescente após o aporte dos tributários. O número de táxons comuns aos 3 rios foi baixo, nos dois períodos de estudo. A alta riqueza de táxons pode ser explicada pela variedade de ambientes amostrados, diferentes tempos de residência da água e de concentração de nutrientes, considerando que os rios Iguaçu e Monday sofrem elevada influência antrópica. A maior abundância de organismos na barragem, em ambos os períodos, ...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Fitoplâncton de água doce; Alga; Paraná, Rio; Limnologia